Characterizing the Binding Sites for GK Domain of DLG1 and DLG4 via Molecular Dynamics Simulation - Li, Hongwei; Chen, Qiong; Shan, Changyu; Guo, Chunling; Yang, Xiuming; Chen, Yingchun; Zhu, Jinwei; Ouyang, Qin (Frontiers in Molecular Biosciences, 2020)
Discs-large (DLG) is a member that belongs to the membrane-associated guanylate kinase (MAGUK) family. The GK domain of DLGs has evolved into a protein–protein interaction module that could bind with kinds of proteins to regulate diverse cellular functions. Previous reports have demonstrated the GK domain of DLGs functioned as a phosphor-peptide-binding module by resolving the crystal structures. Here we investigated into the interactions of DLG1 and DLG4 with their reported phosphor-peptides by molecular dynamics simulations. Post-dynamics analysis showed that DLG1/4 formed extensive interactions with phosphorylated ligands, including hydrophobic and hydrogen bonding interactions. Among them, the highly conserved residues among the DLGs in phosphor-site and β5 sheet were crucial for the binding according to the energy decomposition calculations. Additionally, the binding interactions between DLG4 and reported unphosphorylated peptides including MAP1A and designed GK inhibitory (GKI-QSF) peptides were analyzed. We found the key residues that played important roles in DLG4/unphosphorylated peptide systems were very similar as in DLG4/phosphor-peptide systems. Moreover, the molecular dynamic simulation for the complex of DLG1 and GKI-QSF was carried out and predicted that the GKI-QSF could bind with DLG1 with similar Kd value compared to DLG4/GKI-QSF, which was verified by using ITC assay (Kd = 1.20 ± 0.29 μM). Our study might be helpful for the better understanding of the structural and biological function of DLGs GK domain and encourage the discovery of new binders.